Researching professional practice: The integrated practice perspectives model and continuing education. - Joe F. Donaldson; Gary W. Kuhne (Adult Education Research Conference, 1997)
The "Integrated Practice Perspectives" model reframes previous efforts to link education with professional practice by using theories of situated cognition and learning. Reframing allows other variables in professional performance to be identified, performance to be more thoroughly linked to social and cultural contexts, and a more integrative and deeper conceptualization of professional practice and context to be developed.